2005
DOI: 10.1073/pnas.0407039102
|View full text |Cite|
|
Sign up to set email alerts
|

Structural basis of nonnatural amino acid recognition by an engineered aminoacyl-tRNA synthetase for genetic code expansion

Abstract: The genetic code in a eukaryotic system has been expanded by the engineering of Escherichia coli tyrosyl-tRNA synthetase (TyrRS) with the Y37V and Q195C mutations (37V195C), which specifically recognize 3-iodo- l -tyrosine rather than l -tyrosine. In the present study, we determined the 3-iodo- l -tyrosine- and l -tyrosine-bound structures of the 37V195C mutant of the E. coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 27 publications
2
26
0
1
Order By: Relevance
“…We used a reported crystal structure for the MjTyrRS 36 to inform the diversification of 12 residues in the amino acid binding pocket surrounding the variable side chain of the nsAA (compared with typically six or fewer residues 18,37,38 , with few exceptions targeting nine residues 39 ), and five residues at the aaRS-tRNA CUA anticodon recognition interface (Fig. 3a).…”
Section: Resultsmentioning
confidence: 99%
“…We used a reported crystal structure for the MjTyrRS 36 to inform the diversification of 12 residues in the amino acid binding pocket surrounding the variable side chain of the nsAA (compared with typically six or fewer residues 18,37,38 , with few exceptions targeting nine residues 39 ), and five residues at the aaRS-tRNA CUA anticodon recognition interface (Fig. 3a).…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, in the reported structure, iodoTyrRS- ec recognizes 3-iodo- l -tyrosine by making van der Waals contacts between the mutated residues, Val37 and Cys195, and the iodine atom (Figure 4B). The binding of l -tyrosine to iodoTyrRS- ec , on the other hand, is weakened by the Tyr37Val substitution, which removes the hydrogen bond between the phenolic hydroxyl groups of l -tyrosine and Tyr37 (28) (Figure 4A).
Figure 4.( A ) The amino-acid binding pocket in the crystal structure of iodoTyrRS- ec bound with 3-azido- l -tyrosine.
…”
Section: Resultsmentioning
confidence: 99%
“…Previous structural studies of aminoacyl-tRNA synthetases that recognize unnatural amino acids have shown little change in the backbone structures compared with the WT structure. For example, both the substrate-bound and Tyr-bound structures of a mutant E. coli tyrosyl synthetase that recognizes 3-iodo-L-Tyr have very similar backbone traces as the WT synthetase bound to Tyr (27). The backbone structure of tryptophanyl tRNA synthetase from Deinococcus radiodurans bound to 5-hydroxy-Trp (5HT) is similar to the Trp-bound structure, although the orientation of 5HT in the active site is rotated by almost 180°compared with Trp (28).…”
Section: Comparison With Other Mj Tyrrs Structuresmentioning
confidence: 96%